Repair of pacemaker lead-induced right ventricular perforation via a left mini-thoracotomy. Issue 6 (December 2021) - Uemura, Hisashi; Yajima, Shin; Sekiya, Naosumi; Yamazaki, Sachiko; Satoh, Ayaka; Tanaka, Hiroe; Yamamura, Mitsuhiro; Sakaguchi, Taichi
Abstract: Cardiac perforation is a rare but serious and life-threatening complication of permanent pacemaker implantation, with an incidence of 0.1–6%. Surgery is usually performed through a median sternotomy; however, sternotomy-related morbidity remains a concern. Herein, we report a case of surgical repair performed via a left mini-thoracotomy for a right ventricular perforation caused by implantation of a permanent pacemaker lead in a 56-year-old woman. Through the left fifth intercostal space, the pacemaker lead was observed to have penetrated the left ventricular myocardium, reaching the pericardium. The lead had passed through the right ventricle and the inferior ventricular septum and protruded from the left ventricular myocardium. After pacemaker lead removal, a dark blow-out type hemorrhage occurred; hence, repair was performed using a pair of pledgeted Mattress sutures. In conclusion, left mini-thoracotomy provides an adequate surgical field and has less impact on hemodynamics when operating at the cardiac apex. <Learning objective: Left mini-thoracotomy facilitates easy access to the ventricular apex during in situ management, and also provides an adequate surgical field and has insignificant impact on hemodynamics when operating at the cardiac apex. We also present a detailed surgical movie that reveals a penetrating pacemaker lead, hemorrhage after removing the pacemaker lead, and making a stitch through left mini-thoracotomy.>